Hypertension Culture and Characteristics of P Coastal Communities in East Java viewed from the Dynamics of Health Psychology - Risma Putri Pradani; Mary Philia Elisabeth (Psikostudia : Jurnal Psikologi, 2024)
Hypertension is a dangerous disease or commonly called the silent killer. This is because the symptoms are difficult to observe or appear when the blood pressure is very high or severe. Hypertension is associated with excess salt consumption so that coastal communities may have a high level of susceptibility to hypertension. This study aims to determine the characteristics of P coastal communities in  East Java which are related to high cases of hypertension through the dynamics of health psychology. Health psychology can explain how individual characteristics trigger the emergence of behaviors related to hypertension. The study used a phenomenological qualitative method to explore the characteristics of P coastal communities in East Java. The data were obtained from interviews and observations of health workers, community leaders and residents around the coast. The findings were analyzed using the perspective of the health belief model to understand the emergence of maladaptive behavior so that hypertension becomes a form of vulnerability in society. The results showed that the high cases of hypertension were triggered by the behavior of people who continued to consume any food even though they knew it increased the risk of hypertension. This behavior is triggered by external variables which include demographic data, psychological factors and inappropriate beliefs.Hipertensi merupakan salah satu penyakit yang berbahaya atau biasa disebut dengan silent killer. Hal tersebut dikarenakan gejala yang sulit diamati atau muncul saat kondisi tekanan darah sudah sangat tinggi atau parah. Hipertensi dikaitkan dengan konsumsi garam berlebih sehingga masyarakat pesisir pantai kemungkinan memiliki tingkat kerentanan yang tinggi terhadap hipertensi. Penelitian ini bertujuan untuk mengetahui karakteristik masyarakat pesisir pantai P yang berkaitan dengan tingginya kasus hipertensi melalui dinamika psikologi kesehatan. Psikologi kesehatan dapat menjelaskan bagaimana karakteristik individu memicu munculnya perilaku yang berkaitan dengan penyakit hipertensi. Penelitian menggunakan metode kualitatif fenomenologis untuk menggali karakteristik masyarakat pesisir pantai P. Data didapatkan dari hasil wawancara serta observasi tenaga kesehatan, tokoh masyarakat dan warga disekitar pesisir.  Temuan dianalisis menggunakan perspeksif health belief model untuk memahami tercetusnya perilaku maladaptif sehingga hipertensi menjadi salah satu bentuk kerentanan di masyarakat. Hasil penelitian menunjukkan bahwa tingginya kasus hipertensi dipicu oleh perilaku masyarakat yang tetap mengkonsumsi makanan apapun walaupun mengetahui hal tersebut meningkatkan risiko hipertensi. Perilaku tersebut dipicu oleh variabel eksternal yang meliputi data demografis, faktor psikologis serta keyakinan (belief) yang tidak tepat.